TRANSFORMASI GEN ALBUMIN BUNGA MATAHARI (HELIANTHUS ANNUUS L.) PADA TANAMAN KEDELAI MENGGUNAKAN VEKTOR AGROBAKTERIUM TUMEFACIENS LBA4404 (PAL4404, PSW600) SECARA IN VITRO - SUBERATA, I WAYAN (AGRITROP, 2012)
Usages of A.tumefaciens for the purpose of including DNA sunflower albumine into soybean cell, constituted of natural ability of A. tumefaciens to trasformation in specific form of DNA plasmid (T-DNA) into crop cell later, and then integrate at mains crop cell genome. Result of gene cloning of albumine grown at bacterium of E.coli, then carried over by A. tumefaciens LBA4404, passing method of triparental mating. A. tumefaciens LBA4404 (pAL4404, pSW600) yielded later, then transformation at soybean by in vitro. Result of analysis of transformation at soybean of transgenic by in vitro, can be proved with testing its resilience to gene activity of GUS-its and canamisin.
Keywords: trasformation, sunflower albumine, A. tumefaciens, soybean plants